Integrating Trap Cropping and Entomopathogenic Nematode Foliar Sprays to Manage Diamondback Moth and Imported Cabbage Worm - Sabina Budhathoki; Brent S. Sipes; Ikkei Shikano; Roxana Y. Myers; Roshan Manandhar; Koon-Hui Wang (Horticulturae, 2022)
Diamondback moth (DBM), Plutella xylostella, and imported cabbage worm (ICW), Pieris rapae, are destructive pests of crucifers worldwide. Although several insecticides are effective against ICW, pesticide management against DBM is challenged by insecticide resistant populations. The objective of this study was to explore the potential of integrating foliar sprays of the entomopathogenic nematode (EPN) Steinernema feltiae with trap cropping using kai choi (Brassica juncea) planted as an intercrop for the management of DBM and ICW. Four 2 × 2 (trap crop × EPN) factorial designed field trials were conducted with 2 trials on head cabbage (Brassica oleraceae var capitata) and 2 on kale (Brassica oleraceae var acephala). In the first head cabbage trial, trap cropping reduced DBM abundance by 46% and ICW abundance by 73%. Leaf damage by DBM and ICW were reduced by 45% and 33%, respectively. In the second head cabbage trial, DBM populations were reduced by 19% whereas ICW was reduced by 65%. No effects were observed on leaf damage. Trap cropping suppressed DBM abundance by 50% and DBM leaf damage by 19% in the first kale trial. No significant effects were observed on ICW. In the second kale trial, trap cropping reduced ICW leaf damage by 13%. In the first head cabbage trial, adding EPN foliar sprays further reduced DBM populations in plots with trap crops and ICW in plots without trap crops. In the second kale trial, EPNs suppressed DBM populations entirely. No effects from EPNs were observed in the second head cabbage trial or the first kale trial. It is concluded that trap cropping with kai choi did not improve the efficacy of EPN foliar sprays consistently. EPNs were most successful at suppressing DBM and ICW populations when the average pest pressure was below 0.5/plant whereas trap crops worked more effectively at insect populations above 0.5/plant. Although the use of trap cropping reduced pest abundance and leaf damage, the weight of head cabbage and kale was lower when planted 30 cm or closer to kai choi plants. This was resolved by leaving a distance of 60 cm between cash and trap crops. With further optimization, the use of trap cropping and EPN foliar sprays can be beneficial to an integrated pest management program to control DBM and ICW in cruciferous crops.